Tuberculous lymphadenitis with anthracosis: an unusual cause of unilateral vocal cord paralysis - Ali, Sadaqat; Inam, Hina; Abbasi, Zainab; Hassan, Sulaiman Bashir (International Journal of Endorsing Health Science Research, 2019)
Background: Tuberculous lymphadenopathy is an extremely common condition in developing countries; however, vocal cord paralysis secondary to compression by enlarged tuberculous lymph node is an extremely rare presentation. Case Presentation: In this paper, we present the case of a 72-year-old male patient who came to us with concerns of hoarseness of voice for the last eight months with fever and chills. He had been treated previously at ear, nose and throat (ENT) clinics and on evaluation, we discovered he had left vocal cord paralysis. Imaging showed multiple enlarged mediastinal and right hilar lymph nodes. Management & Results: Mediastinoscopy with biopsy was done and after histopathologic confirmation of tuberculosis, the patient was prescribed antituberculous treatment. Conclusion: Antituberculous treatment in such patients shows signs of clinical and radiologic improvement.